Long-term local control and survival after preoperative radiochemotherapy in combination with deep regional hyperthermia in locally advanced rectal cancer. (17th February 2016) - Gani, Cihan; Schroeder, Christopher; Heinrich, Vanessa; Spillner, Patrick; Lamprecht, Ulf; Berger, Bernhard; Zips, Daniel
Abstract: Purpose : The aim of this study was to evaluate the impact of deep regional hyperthermia on long-term local control and survival in locally advanced non-metastatic rectal cancer. Methods : In total 103 patients with locally advanced non-metastatic rectal cancer were treated preoperatively with either neoadjuvant radiochemotherapy alone ( n  = 43) or the same treatment with additional deep regional hyperthermia ( n  = 60). The two groups were compared with respect to local control, overall survival (OS), disease-free survival (DFS), and distant metastases-free survival (DMFS). Results : Patients receiving additional hyperthermia had excellent long-term local control with a 5-year Kaplan-Meier estimate of 98% compared with 87% in the radiochemotherapy only group ( p  = 0.09). Five-year rates for OS (88% versus 76%, p  = 0.08), DFS (77% versus 73%, p  = n.s.) and DMFS (75% versus 77%, p  = n.s.) were not statistically different between the two groups. Conclusion : Radiochemotherapy combined with hyperthermia results in excellent long-term local control.